Signaling mechanisms essential for reactivation of latent herpes simplex virus type 1 in neuronal cultures - Hunsperger, Elizabeth Anne, author; Wilcox, Christine, advisor (Colorado State University. Libraries, 2002)
Herpes simplex virus type 1 belongs to the herpesviridae sub-family alphaherpesvirinae. This family of viruses is recognized by their ability to establish a lifelong latent infection in humans. Although generally not life threatening, HSV-1 has adapted to its human host with perfect precision. Latency and reactivation remain a mystery to scientists to date. The only cells that establish a latent infection are sensory neurons. This cell type specificity and the mechanisms of reactivation remain unclear. The experiments and studies presented here attempt to elucidate a potential unifying hypothesis of herpes reactivation that involves calcium modulation in the nociceptor neuron. Calcium is a highly regulated ion in neurons with pleiotropic effects. The diverse roles of calcium in the neuron allow it to change the membrane potential towards depolarization and also signal apoptosis. Many of the known stimuli both in humans and in our culture system cause an increase in intracellular calcium levels and ultimately lead to herpes reactivation. These secondary pathways include activation of protein kinase C (PKC), protein kinase A (PKA), vanilloid receptor-1 (VR-1) activation, nerve growth factor (NGF) deprivation and heat shock. Studies presented here focused on the pain receptor, VR-1. VR-1 is a calcium ion channel found primarily on nociceptor neurons. Its activation results in herpes reactivation that is reversible with the specific inhibitor to VR-1, capsazepine. We tested two different agonists, heat stimulus exceeding 45°C and capsaicin. Both agonists caused herpes reactivation with different kinetics. Capsaicin treatment resulted in a bell-shaped dose response curve that could be attributed to desensitization of the channel. Whereas heat stimulation yielded significant increase in reactivation for temperatures that were permissive for VR-1 activation. Additionally, NGF withdrawal experiments indicated that the pro-apoptotic protease enzyme, caspase-3 plays a pivotal role in herpes reactivation. Caspase-3 exists as a pro-enzyme in the cytoplasm of the cell and upon activation to its catalytic form, it translocates to the nucleus where its major role in DNA fragmentation takes place. Our studies showed that inhibition of caspase-3 following NGF deprivation attenuated but did not abolish HSV-1 reactivation. In order to address the direct role of caspase-3 in HSV-1 reactivation, we treated the neurons with C2-ceramide and over-expressed caspase-3 with a recombinant adenovirus. Both of these treatments induced HSV-1 reactivation in our model suggesting a direct role of caspase-3. In conclusion, calcium homeostasis is essential for neuronal survival, signaling and plasticity. Disruption of this homeostasis through various stimuli that excite the nociceptor neuron may lead to reactivation. This disruption modulates neuronal excitability rendering the neuron more susceptible to herpes reactivation in response to a milder stress stimulus.
Keywords: microbiology